Trabalho docente : formação como experienciação - Altoé, Alini (2019)
It discusses the formation of teachers as a production of subjectivity, which allows deviations and reappropriations in front of school and life regulations, making it possible to open fissures, and produce other ways of being a teacher, that break with the transmission of information and the acquisition of skills. It proposes an intervention research, from the constitution of a group of teachers of the Instituto Federal do Espírito Santo, Campus São Mateus, in which the researcher and participants, through conversations and records in field diaries, while producing collective analyzes that consider the aspects that cross the school and the processes of teaching and learning, interfere in the investigated reality, being able to attend to the minutiae of the teaching work and to experience other ways of teaching and learning. It defends a cognitive policy of invention, as a possibility, in which training is considered processuality which opens up possibilities for problematizations, denaturalizations and the production of other ways of teaching work that surpass recognition. In this way, it exposes clues of the teachers ways that emerge in this school, and also shows how to strengthen the formative processes that value the problematizations and overcome the hegemonic models of being a teacher in favor of other ways of thinking, to create, to feel, to act and to live.